2019
DOI: 10.31410/balkans.jetss.2019.2.1.80-87
|View full text |Cite
|
Sign up to set email alerts
|

The Customers’ Perception of the Sellers in the Context of Gender Differences​

Abstract: Personal selling has its own specifics and allows sellers to interact directly with the customer. The aim of the proposed paper is to find out statistically significant differences in the perception factor affecting personal selling from the customer’s perspective in the context of gender differences. A differential analysis was conducted on the sample of 243 respondents (112 male customers and 131 female customers); on the basis of the data obtained by means of an original methodology for detecting the factor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2022
2022

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 4 publications
0
3
0
Order By: Relevance
“…It can be noted that gender differences in the area of business and trade were also part of the study by [40], who found statistically significant gender differences in the perception of personal selling from the customer's perspective. Another study by [41] was evaluated consumer shopping behavior in the context of gender equality.…”
Section: Discussionmentioning
confidence: 95%
“…It can be noted that gender differences in the area of business and trade were also part of the study by [40], who found statistically significant gender differences in the perception of personal selling from the customer's perspective. Another study by [41] was evaluated consumer shopping behavior in the context of gender equality.…”
Section: Discussionmentioning
confidence: 95%
“…The acquisition of knowledge and appropriate social habits was also possible due to the inclusion of non-traditional, innovative teaching methods. Social learning has contributed to the analysis of the students' own behaviour in demanding situations, as well as the behaviour of the group as a whole (Kovaľová et al, 2019).…”
Section: Methodsmentioning
confidence: 99%
“…Keyes (2002) defined three factors that speak of the presence of mental health, namely emotional well-being, which is characterized by the predominance of positive emotions in a person's life, psychological well-being, and social well-being, which is composed of five factors (Keyes & Lopez, 2002) -Social coherence, Social acceptance, Social actualization, Social contribution, and Social integration. These factors will be examined in the following contribution in the context of perception of social well-being in trade, particularly among customers (as defined in Kovaľová et al, 2019) and leaders of trade who continually experience pressure and need to find a way to cope with demanding business situations.…”
Section: Personal Well-being = Positive Emotions -Negative Emotions +...mentioning
confidence: 99%